Proyecto de factibilidad para la creación de una empresa productora y comercializadora de ropa deportiva sobre medida, en la ciudad de Loja, periodo 2022 - Condo Ramon, Leidy Lizbeth (2023)
The project focuses on determining the feasibility for the creation of a company dedicated to the production and marketing of custom-made sports apparel in the city of Loja. The research adopts a descriptive nature with a qualitative and non-experimental quantitative approach, enabling the collection of information and presentation of results. The study population consisted of individuals aged 15 to 49 in Loja city, representing 48.10% of the total population, which amounts to 112,098. The survey conducted among potential customers provided crucial information to determine the project's market acceptance, identify unmet demand, potential demands, as well as real and effective demands. Further to this, an analysis was conducted on installed capacity, utilization, location, infrastructure, and various technological components. In the financial study, the investment amounts to $22,897.79, with $12,897.79 contributed by the investors, and $10,000 financed by Banco Pichincha at an annual interest rate of 11.26%. Financial results indicate a Net Present Value (VAN) of $30,285.27, a positive Internal Rate of Return (TIR) of 54.28%, a Benefit- Cost Ratio of 0.20, and a capital recovery period of 4 years, 5 months, and 16 days. Sensitivity analysis reveals that the project can withstand increases in costs and decreases in revenue percentages. Based on all the aforementioned results, it is determined that the project is both feasible and viable.